Online Health Search Experience: Sentiments from South East Asia - Inthiran, Anushia (International Journal of Knowledge Content Development & Technology, 2016)
Online health information searching is a popular activity performed on the Internet. Research studies from developed countries provide information on the type of person who performs the search, source used, type of search performed and devices used to perform the search. However, the same cannot be said about the online health information searching scene in South East Asia. Online health information searching is gaining popularity in South East Asia. Citizens in these countries are turning to the Internet to obtain health information quickly. Current research studies pertaining to online health information searching in South East Asian is limited, particularly relating to search experience of South East Asian health searchers. Search experience is pertinent as it could deter or encourage the possibility of conducting future health searches. In this research study, we conducted a user study to describe the online search experience of South East Asian health searchers. We conducted a face to face interview with 50 participants. The interview was audio recorded and transcribed verbatim. Results indicate participants experience positive and negative search experience. In some cases, post search outcomes influenced the search experience. Results of this research study contribute to the growing domain of knowledge in relation to online health information searching. It also provides an understanding pertaining to the search experience of South East Asian online health searchers. URL: http://ijkcdt.net/xml/08902/08902.pdf